Mother-Child Play During the COVID-19 Pandemic: Just Stay at Home - Sari, Diah Andika; Rahmatunnisa, Sriyanti; Yulianingsih, Ika (Universitas Negeri Semarang, 2021)
This study aims to determine which types of activities are mostly played by mothers and their children during â€œjust stay at homeâ€ or since the implementation of the Large-Scale Social Restrictions (PSBB). Starting on March 16, 2020, the PSBB has enforced by the DKI Jakarta and other local governments in Indonesia to overcome the Covid-19 pandemic. The study was conducted by survey method, using a questionnaire of Google form application. The questionnaire was distributed online from 9 to 20 April 2020. As a sampling technique, purposive sampling was selected, including mothers who have children between the ages of 2-8 years. A total of 545 participants were obtained through WhatsApp, Instagram, and Facebook. The results of the study showed that there were five types of activities mostly played by mothers and their children: 1) reading, writing, and math, 2) watching YouTube, 3) life skills, 4) two and three-dimensional arts, 5) playing water. While the types of activities rarely played: 1) playing gadgets, 2) science experiments, 3) light sports. In similar, there were three types of activities rarely played: 4) home materials creativity, 5) traditional games, 6). Storytelling / fairy tales / drama, 7) music and movement. Referring to the finding, it was a positive significant result because the gadget was the rare play. These might occur because majority respondents were highly educated and working as educators in particular.